The value is 1 if (x, y) = (4, 3) and 0 otherwise.
To find the value of y in the expression 15y-4 = 41, you need to isolate y. Start by adding 4 to both sides of the equation to get 15y = 45. Then, divide both sides by 15 to solve for y, which equals 3. Therefore, the value of y in the expression 15y-4 when it equals 41 is 3.
If you mean: x^2+15-3x then its value is 19 when x equals 4
2 squared is 4 3 cubed is 27 27 plus 4 is 31
(21-3)times(7+4)
The value is 1 if (x, y) = (4, 3) and 0 otherwise.
You don't, unless you know either the value of x or what the expression equals.
The answer is -369.
To find the value of y in the expression 15y-4 = 41, you need to isolate y. Start by adding 4 to both sides of the equation to get 15y = 45. Then, divide both sides by 15 to solve for y, which equals 3. Therefore, the value of y in the expression 15y-4 when it equals 41 is 3.
-4 (-9 +5 = -4)
If you mean: x^2+15-3x then its value is 19 when x equals 4
72/c where c= 4 is the same as 72/4 (which =18)
2x^2+3xy-4y2(4)+3(2)(-4)-(4)(-4)8-24+16=0
To find the value of (n-2)^2 + n-1 when n=4, we simply substitute 4 for n in the expression: (n-2)^2 + n-1 When we do this, the expression becomes: (4-2)^2 + 4-1 Now we need to simplify the expression within the parentheses first. The expression within the parentheses is (4-2)^2, which means we need to subtract 2 from 4 and then square the result. So, we get: 2^2 Which equals 4. Now we can substitute this value back into the original expression to get: 4 + 4-1 Next, we simplify the expression 4-1, which equals 3. So, the expression becomes: 4 + 3 And we can simplify that further to get: 7 So, when n=4, the value of (n-2)^2 + n-1 is 7
2 squared is 4 3 cubed is 27 27 plus 4 is 31
That depends on the value of x in the given expression
To find the value of the expression 4x - 2y + xy when x = -1 and y = 5, we first substitute the values of x and y into the expression. This gives us 4(-1) - 2(5) + (-1)(5). Simplifying this further, we get -4 - 10 - 5, which equals -19. Therefore, the value of the expression is -19 when x = -1 and y = 5.